Deviant Citizenship: DREAMer Activism in the United States and Transnational Belonging - Joaquina Weber-Shirk (Social Sciences, 2015)
My analysis places the assertions of political presence by non-citizen immigrant youth in the U.S. (often referred to as DREAMers) within a rapidly globalizing world; this placement re-frames the DREAMers’ movement from a fight for U.S. citizenship to a broader critique of the limits and impossibility of liberal democratic citizenship, which claims to be all-inclusive. Increased transnational migration has brought into stark relief the inequality that current frameworks of nation-state citizenship, as a caste-system of rights, have codified. I am interested in the activism of immigrant youth as a place to explore where immigrants themselves are reasserting the right to politics. This reassertion privileges the social embeddedness of family ties and community above the notion of individual choice or individual rationality. In doing so, this articulation of politics is a critique of the liberal order by forcing the consideration of the contexts and structures that create migration, exploitation, and transnational communities of belonging.